2015
DOI: 10.1136/heartjnl-2015-307782
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of NT-proBNP in heart failure with preserved versus reduced EF

Abstract: Plasma level of NT-proBNP is the most powerful prognostic factor in both HFpEF and HFrEF. Although patients with HFpEF have lower NT-proBNP levels, the prognosis of a patient with HFpEF expected from a given NT-proBNP level is similar with his/her counterpart with HFrEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 33 publications
7
94
0
6
Order By: Relevance
“…BNP levels are associated with HF severity and are a reliable predictor of prognosis throughout the stages of HF 9, 10, 11. In addition, recent reports show that elevated BNP levels are associated with poor prognosis in patients with HFpEF as well as in those with HFrEF 12, 13. Accordingly, the current study investigated the heterogeneity of clinical features associated with HF and the prognostic value of BNP levels in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 94%
“…BNP levels are associated with HF severity and are a reliable predictor of prognosis throughout the stages of HF 9, 10, 11. In addition, recent reports show that elevated BNP levels are associated with poor prognosis in patients with HFpEF as well as in those with HFrEF 12, 13. Accordingly, the current study investigated the heterogeneity of clinical features associated with HF and the prognostic value of BNP levels in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 94%
“…ROC analysis of 6-month death further showed that CCN1 could predict events in AHF patients as effectively as NT-proBNP. NT-proBNP that is released in response to volume expansion and pressure overload is a well-established biomarker in predicting heart failure [27,28], and CCN1 has been shown to be involved in the regulation of fibrogenesis associated with cardiac remodeling. The use of a combination of biomarkers associated with different pathophysiological pathways could produce additive prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Kang et al analyzed 528 HFpEF and 1,142 HFrEF patients from the KorHF registry, and showed that the plasma level of NT-proBNP is a powerful prognostic factor in both HFpEF and HFrEF. 20 In addition, we controlled the effect of LVEF in multivariable analysis. Therefore, it may be hard to consider a higher incidence of HFpEF in women than in men as a potential mechanism for gender-specific value of NT-proBNP.…”
Section: Fundingmentioning
confidence: 99%